Does Child Sponsorship Pay off in Adulthood? : An International Study of Impacts on Income and Wealth - Wydick, Bruce; Glewwe, Paul; Rutledge, Laine (Published by Oxford University Press on behalf of the World Bank, 2018)
We estimate the impact of international child sponsorship on adult income and wealth of formerly sponsored children using data on 10,144 individuals in six countries. To identify causal effects, we utilize an age-eligibility rule followed from 1980 to 1992 that limited sponsorship to children twelve years old or younger when the program was introduced in a village, allowing comparisons of sponsored children with older siblings who were slightly too old to be sponsored. Estimations indicate that international child sponsorship increased monthly income by $13–17 over an untreated baseline of $75, principally from inducing higher future labor market participation. We find evidence for positive impacts on dwelling quality in adulthood and modest evidence of impacts on ownership of consumer durables in adulthood, limited to increased ownership of mobile phones. Finally, our results also show modest effects of child sponsorship on childbearing in adulthood.